Virtual ethnography methodology for researching networked learning - Charnet, Chantal; Veyrier, Clair-Antoine (Proceedings of the International Conference on Networked Learning, 2008)
This article describes the application of a qualitative method based on digital ethnography in research on networked learning in Higher Education. The proposed method tends towards a solution for the need of innovative techniques for the study of new forms of interaction emerging in computer supported collaborative learning (CSCL) and their effective uses. It is based on three phases: first, initial exploration and systematic collection, then, organisation and comparison of data, and finally, analysis. The corpus is composed of various data (audio-visual recordings, images, texts): audio-visual and textual data are organised and compared. The results suggest that an analysis of the process in its development is possible. The interpretative course is built thanks to the effective situations of uses. The ethnographical methodology applied to the study of the technological environment brings a concrete visibility of the implementation tracks and manners. It gives the possibility of having access to the development of the non stop process. Taking into consideration all the constituent elements allows to encircle the diverse activities of the actor. It permits to analyse phenomena that would be invisible with a quantitative method. We took into account the digital specificity of the observed object. So the following methodology joins in an ethnographical observation of sequences of activities recorded in context of the different situations, and uses of these devices. This frame of continuous observations requires the participation of the researchers during the whole process. The data collection reports the course and the integration of devices in the considered organisation. Thus we turned to a collection of diversified data which offers the possibility of a direct observation of situations that are in the field of the anticipation or of the stabilized use. The methodology of the research is articulated in three phases: first, exploration, then systematic collection, location, organization and linkage of the data, and finally, analysis (Crabtree 2003). The analysis does not occur only at the end but during the whole process of research. During the first phase of exploration, a participant observation is used and provides the opportunity to collect data that are not easily accessible by using other methods (Paterson 2003, p.4). Fieldnotes gives general view of the process. But the analysis of the process is monitored through systematic recording of the activities. Our direct observation was supported, by recordings. We can distinguish two kinds of recordings. First of all, the logs that the technical framework permits to collect. The institutional logs of the virtual learning environment constitute the first source of that kind of information. But the ethnographical methods enable to enlarge the collection of log data: the record of the ecological context. We can distinguish two levels of context which need different techniques of recording of the ecology : computer screen recording and video-taping of the student working on an activity. The data contents are then tracked down and organised to allow the constitution of a corpus which constitutes the maximal unit in which it will be possible to build interpretative routes. The detailed study of the episodes shows how every stage is essential for the construction of manners and participates in the direction given to these numeric manners. Many of these phenomena only emerge after repeated viewing video tapes or other data. The ethnographical methodology applied to the study of the technological environment brings a concrete visibility of the tracks of implementation and manners, and gives the possibility of having access to the development of the non stop process.